Simulation of Voltage and Frequency Stabilization in PV-Based Microgrids Using Virtual Synchronous Generator Control - Zaw Tway Oo (The Indonesian Journal of Computer Science, 2024)
In recent years, distributed generation technologies and micro-grids have garnered increasing attention, particularly with the rapid growth of renewable energy sources (RESs) integrated via power electronic converters. As the penetration of RESs in modern power systems rises, voltage and frequency support, traditionally provided by synchronous generators, can be effectively managed by Virtual Synchronous Generator (VSG) control. This paper presents the modeling and analysis of voltage and frequency stability enhancement in a PV-based micro-grid system using VSG control. The micro-grid system under study operates at 400V, 50Hz, and is integrated with a 0.4kV power distribution line. Mathematical models of the VSG control strategy are developed in MATLAB/Simulink. Simulation results demonstrate that VSG control significantly improves the voltage and frequency stability of the PV-based micro-grid system.